Comparative genomics of brain size evolution - Enard, Wolfgang (Frontiers in Human Neuroscience, 2014)
Which genetic changes took place during mammalian, primate and human evolution to build a larger brain? To answer this question, one has to correlate genetic changes with brain size changes across a phylogeny. Such a comparative genomics approach provides unique information to better understand brain evolution and brain development. However, its statistical power is limited for example due to the limited number of species, the presumably complex genetics of brain size evolution and the large search space of mammalian genomes. Hence, it is crucial to add functional information, for example by limiting the search space to genes and regulatory elements known to play a role in the relevant cell types during brain development. Similarly, it is crucial to experimentally follow up on hypotheses generated by such a comparative approach. Recent progress in understanding the molecular and cellular mechanisms of mammalian brain development, in genome sequencing and in genome editing, promises to make a close integration of evolutionary and experimental methods a fruitful approach to better understand the genetics of mammalian brain size evolution.